Improving Student Learning Outcomes in Islamic Education Learning Using the Think Pair Share Type Cooperative Model at SD Negeri No. 10 in 2013 Sialang Buah - Rahim, Abdur; Hayati, Junainah (MANDAILING GLOBAL EDUKASIA, 2024)
This classroom action research was driven by the low learning outcomes of fifth-grade students at SD Negeri No. 102013 Sialang Buah in the subject of Islamic Religious Education and Ethics, particularly on the topic of Faith in the Book of Allah. Initial observations revealed that most students struggled to understand the basic concepts and demonstrated low participation during lessons. To address this issue, the study aimed to improve student learning outcomes by applying the Think Pair Share (TPS) cooperative learning model, which emphasizes student engagement through individual thinking, paired discussions, and group sharing. The research was conducted in two cycles, each comprising planning, action, observation, and reflection phases. A total of 24 students participated in the study. Data were collected through learning outcome tests, teacher and student observation sheets, and documentation, and were analyzed both qualitatively and quantitatively. The results showed that the implementation of the TPS model led to a notable improvement in student learning outcomes, evidenced by increased average test scores and a higher percentage of students achieving mastery from cycle I to cycle II. Additionally, student activity during lessons improved significantly, particularly in cognitive engagement and collaborative participation. These findings indicate that the TPS model is effective in enhancing understanding and fostering a more interactive and enjoyable learning environment. Consequently, it is recommended that the Think Pair Share model be adopted as an innovative and participatory approach in teaching Islamic Religious Education at the elementary level, especially for conceptual topics such as Faith in the Book of Allah.